Perlindungan Hak Asasi Pasien Hemodialisis di Masa Pandemi Covid-19: Protection of the Human Rights of Hemodialysis Patients during the Covid-19 Pandemic - Saija, Vica Jillyan Edsti; Lumintang, Junior Alvaro Nazario (Fakultas Hukum Universitas Negeri Semarang, 2021)
Indonesia recognizes and guarantees that health is a human right, the basic regulation of which is written in Article 28H paragraph (1) of the 1945 Constitution of the Republic of Indonesia, namely that every person has the right to live in physical and mental prosperity, have a place to live, and have a good living environment. and healthy and entitled to health services. In realizing the implementation of human rights, it can be interpreted based on the further provisions in Article 28I paragraph 4, this is the responsibility of the state, especially the government. The regulation of responsibility for public health through the provision of its service facilities is further emphasized in the provisions of Article 34 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. Since the Covid-19 pandemic hit Indonesia in 2020, health care is one of the areas with a major impact. The anomalous situation that occurs also affects the blood washing schedule for hemodialysis patients who have difficulty getting access to health services and are not even served properly, and the consequences of not doing hemodialysis routinely will be dangerous for these patients. This paper wants to examine how the government is responsible for protecting human rights of hemodialysis patients during the Covid-19 pandemic. The writing method used is normative with a problem approach that is based on statutory regulations, concepts, and cases.